COMMUNITY SATISFACTION INDEX (CSI) ON STUDENTS’ DA’WAH PRACTICUM PROGRAM AT CIPAYUNG, EAST JAKARTA - Giyanti, Ummu Ahya (Jurnal Bina Ummat: Membina dan Membentengi Ummat, 2025)
This study aims to determine the Community Satisfaction Index (CSI) on Students’ Da’wah Practicum Program at Cipayung, Jakarta Timur. This program is conducted by STID Mohammad Natsir in partnership with Taman Pendidikan AL Qur’an (TPA in Cipayung, Jakarta Timur. The research approach used descriptive quantitative. The results of the study showed that the average score of community satisfaction with the assistance carried out by STID Mohammad Natsir students in Da’wah Practicum Program was good with a scale of 3.975 and a conversion score of 79.506. The indicator of satisfaction is seen from five aspects, namely tangibles, an average score of 4.296 equivalent to 85.913 is at a very good level; empathy was  3.775 equivalent to  75.507 and was good; Reliability indicator had  an average score of 3.832 equivalent to  76.630 and  was good; responsiveness  indicator had an average score of 3.887 equivalent to  77.739 and was good; the last, assurance  indicator had an average score of 4.087 equivalent to  81.739 and was good level. From the score of the five aspects, the Community Satisfaction Index (CSI) score was 78.98, with a scale conversion of 3.949. From these results, it is concluded that student assistance in Da’wah Practicum Program received a good response from the community. This already good response needs to be improved so that the level of satisfaction of partner institutions will continue to rise.